Students’ Perception Toward Teachers’ Implementation of Technological Pedagogical and Content Knowledge (TPACK) in EFL Classroom at Madrasah Aliyah - Asmul Hayati; M. Zaim (STAI Hubbulwathan Duri, 2024)
Technology and education are two things that influence each other. Technology in education is not only about the tools, applications, and software but also about how the teachers integrate the technology to present the learning model and learning content in learning activity. Therefore, this research aimed to find out the students’ perceptions toward teachers’ implementation of technological pedagogical and content knowledge (TPACK) in EFL classroom. This research is descriptive research and was located at one of madrasah Aliyah in Pekanbaru. There were 106 tenth-grade students as the respondents. A questionnaire is used to collect the research data on students’ perceptions. The finding revealed that students’ perception toward teachers’ implementation of TPACK in EFL classroom is positive perception, with a total mean score is 3.02, which means EFL students have a positive perception about teachers’ implementation of TPACK in EFL classrooms. Based on this result, it can be said that the teachers have the ability and the awareness related to the importance of implementing TPACK to support the teaching and learning process, especially to increase students’ comprehension and motivation in learning English.